Oro‐dental features in Egyptian patients with familial mediterranean fever. (13th December 2021) - Abouzaid, Maha; Hassib, Nehal; Hamed, Khaled; Taher, Mohamed; Sokkar, Mona; Eltaweel, Noha; El‐Bassyouni, Hala
Abstract: Introduction: Familial Mediterranean fever (FMF) is an episodic inflammatory disease that is inherited as an autosomal recessive trait. It is primarily featured by fever, pain in joints, chest, and abdomen due to Serositis. Aim: This study delineated the oro‐facial structures presented associated with FMF, as well as, the determination of the potential influences of the long‐term inflammatory process of FMF on several oral structures. Methods: Fifty eight Egyptian FMF patients were examined to define different oro‐facial structures. Serum amyloid A (SAA) was requested for the selected patients, MEFV gene mutation was also investigated. Results: The clinical examination revealed peritonitis in 79%, fever in 63.7%, and arthritis in 55% of FMF patients examined, while, oral features as high arched palate, enamel defect, dental malocclusion, and macroglossia in 32%, 27.5%. 26%, and 13.5%, respectively. The previous symptoms might be attributed to the pathology of the disease. Macroglossia when tested versus SAA levels, a highly significant difference was detected. The ROC curve when examining the SAA value to assess macroglossia, displayed reasonable sensitivity and specificity values of, 87.5% and 77.8%, respectively. Conclusion: The noticed oro‐dental in FMF patients might be influenced by the chronic inflammatory process.